Between artisans and coolies. Trinidad Manuel Perez (1832-1879), a first author of social recognitions in Peru - Zevallos, Johnny (2018)
The work, practically unknown, of journalist from Trujillo Trinidad Manuel Pérez has had to submit to oblivion on part of the literary criticism; however, it contains innovative elements such as the insertion of new subjects as artisans, coolies, bandoleros, and female readers. Our intention is to analyze his dramatic pieces El emigrado español (1859) and La industria y el poder (1862), as well as his unfinished novel Nurerdin-Kan (1872), first production that records the immigrationof the Chinese people to Peru in order to claim the social struggles and the participation of peoples from the incorporation of innovative liberalism.